Pengaruh Kualitas Pelayanan dan Harga terhadap Kepercayaan sebagai Variabel Mediasi terhadap Loyalitas Konsumen pada Aero Coffee Balikpapan - Agung Widiyanto; Amirruddin Amirruddin; Hijir Ismail Aziz; Syahril Hasan (Lembaga Teewan Journal Solutions, 2026)
This study examines the effects of service quality and price on customer loyalty, with trust as a mediating variable, at Aero Coffee Balikpapan. Increasing competition among coffee shops has encouraged businesses to improve customer satisfaction and retain loyal customers through better service, competitive pricing, and stronger trust. This research employed a quantitative explanatory approach involving 65 customers selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with a bootstrapping procedure to examine direct and indirect relationships among variables. The results indicate that both service quality and price have a positive and significant effect on customer trust. Trust also has a positive and significant effect on customer loyalty and mediates the relationship between service quality, price, and customer loyalty. These findings suggest that improving service quality and offering prices that match customers’ value perceptions can strengthen trust and foster long-term customer loyalty. Therefore, Aero Coffee Balikpapan should continue enhancing service quality, implementing competitive pricing strategies, and maintaining customer trust to achieve sustainable business growth.